Mass Spectrometry-Based Proteomics to Unveil the Non-coding RNA World - Giambruno, Roberto; Mihailovich, Marija; Bonaldi, Tiziana (Frontiers in Molecular Biosciences, 2018)
The interaction between non-coding RNAs (ncRNAs) and proteins is crucial for the stability, localization and functions of the different classes of ncRNAs. Although ncRNAs, when embedded in various ribonucleoprotein (RNP) complexes, control the fundamental processes of gene expression, their biological functions and mechanisms of action are still largely unexplored. Mass Spectrometry (MS)-based proteomics has emerged as powerful tool to study the ncRNA world: on the one hand, by identifying the proteins interacting with distinct ncRNAs; on the other hand, by measuring the impact of ncRNAs on global protein levels. Here, we will first provide a concise overview on the basic principles of MS-based proteomics for systematic protein identification and quantification; then, we will recapitulate the main approaches that have been implemented for the screening of ncRNA interactors and the dissection of ncRNA-protein complex composition. Finally, we will describe examples of various proteomics strategies developed to characterize the effect of ncRNAs on gene expression, with a focus on the systematic identification of microRNAs (miRNAs) targets.